Assessment of storage related hematological and biochemical changes of citrate phosphate dextrose adenine-1 whole blood - Dr. Bhaswanth. P; Dr.B.R.Yelikar (International Journal of Pharma and Bio Sciences, 2020)
Blood can be stored under refrigeration in preservative solutions such as citrate phosphate dextrose adenine (CPDA- 1) solution for up to 35 days. The goal of blood preservation is to provide viable and functional blood components for patients who need blood transfusion. Transfusion of stored RBCs, particularly those at the end of the approved shelf life, undergo numerous biochemical, metabolic, hematological, which results in irreversible damage with the concomitant release of potentially hazardous bioactive products referred to as RBC storage lesion. Considering above discussed facts, a cross-sectional study was carried out on stored CPDA-1 whole blood to determine the changes during different storage periods. Analysis of variance (ANOVA) showed that at the end of 28 days, there was a significant decrease in WBC (P<0.01) and platelet count (P<0.01). Plasma potassium levels (P<0.01) significantly increased from day 0 to day 28. No significant changes were observed in other parameters. The study indicated that rapid degeneration of WBCs could lead to immunomodulation. Therefore, whole blood should be leukodepleted before storage. Blood units with pre-existing high potassium values should be considered for early release from blood banks to prevent transfusion related hyperkalemia.